Traditional and Innovative Approaches in Seismic Design - Linda Giresini (ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
This special issue collects selected papers about a wide range of innovative applications in earthquake engineering. These studies were presented during the 2nd Edition of the International Workshop "Traditional and Innovative Approaches in Seismic Engineering", held in Pisa in March 2017. The topics refer to the investigation of traditional and innovative materials for earthquake engineering applications: masonry, reinforced concrete, steel, structural glass and timber. In particular, advanced analytical and numerical analyses are described for considering effects of strength and material irregularities and rocking behavior under seismic excitations on historic buildings and industrial facilities. Experimental tests are also illustrated with the purpose of investigating the strengthening on masonry arches due to lime-based mortar composites and of obtaining reliable values of stiffness for moment resisting steel-timber connections. Among the innovative approaches, studies on original pavilions made of long-spanned TVT-portals braced with hybrid glass-steel panels are illustrated